Gaze behavior is influenced by task demands rather than football players creativity - Christian Vater; Svitlana Pinchuk; Stephan Zahno (Bern Open Publishing, 2024)
Introduction The "most creative" football players seem to make more fixations of shorter durations than "least creative" players, indicating a broader attentional focus (Roca et al., 2018, 2021). In these studies, however, players are classified as "creative" based on their ability to name many, diverse and unusual solutions rather than to execute these options and they were only provided with a third-person viewing perspective when making decisions. In our study, funded by a FIFA scholarship, players experienced a first-person viewing perspective and when executing their most functional solution in virtual-reality game scenarios. Contrasting the idea of a distinct gaze strategy generally used by creative players, we expected that task demands would better explain gaze behavior than creativity. Methods We developed an immersive, 360° virtual reality (VR) setup using the Unreal engine to animate real football scenes and a 6 x 12 m cave-like laboratory with wall and floor projections. In five "mother scenes", the location of teammates off the ball was systematically manipulated leading to 80 trials; each being occluded 1 s after the virtual ball was at the participants' foot. We examined the originality, decision-quality, and creativity of the participants' initial response; response time and gaze behavior (i.e., average number of fixations, the time interval between fixations, and the distance between fixations to examine the breadth of fixations). We expected that distances would be large when scanning the environment and small shortly before and after the ball must be played. Based on expert ratings of players' executed options, we ranked participants to a more (n = 7) and less creative group (n = 7). Groups were significantly different in overall creativity (p < .0001), originality (p < .0001) and quality (p < .001). Results The results show that groups did not differ in response times (p = 0.34), mean number of fixations (p = .48) or mean fixation duration (p = .68). The fixation distance in the entire trial was significantly higher than shortly before (p < 0.01) or shortly after (p < 0.01) the (virtual) ball is received, with no difference between more and less creative players. There was a significant difference in fixation distances for the 5 "mother scenes" (p < 0.01). Discussion/Conclusion All players, not only the creative ones, have a wide fixation pattern before the ball is played to them, presumably to identify the most functional passing option. They then concentrate on the reception of the ball with a narrow fixation pattern. This pattern remains also in the pass execution phase. Creative players seem to better select and execute the best (and most creative) option rather than showing a distinct gaze behavior. Overall, our results suggest that players should be able to adjust their gaze pattern to the task demands to foster creative actions. References Roca, A., Ford, P. R., & Memmert, D. (2018). Creative decision making and visual search behavior in skilled soccer players. PLoS One, 13(7), Article e0199381. https://doi.org/10.1371/journal.pone.0199381 Roca, A., Ford, P. R., & Memmert, D. (2021). Perceptual-cognitive processes underlying creative expert performance in soccer. Psychological Research, 85(3), 1146-1155. https://doi.org/10.1007/s00426-020-01320-5